2006
DOI: 10.1016/j.jmaa.2005.05.064
|View full text |Cite
|
Sign up to set email alerts
|

Generating limit cycles from a nilpotent critical point via normal forms

Abstract: It is well known that the normal form theory can be applied to solve the center-focus problem for monodromic planar nilpotent singularities. In this paper we see how this theory can also be applied to generate limit cycles from this type of singularities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 14 publications
0
72
0
5
Order By: Relevance
“…To the best of our knowledge, there are essentially three different ways, the normal form theory [6], the Poincaré return map [12] and Lyapunov functions [13], of studying the center-focus problem of nilpotent critical points, see for instance [3,14,15]. On the other hand, the three tools mentioned above have been also used to generate limit cycles from the critical point, see for instance [15][16][17], respectively.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there are essentially three different ways, the normal form theory [6], the Poincaré return map [12] and Lyapunov functions [13], of studying the center-focus problem of nilpotent critical points, see for instance [3,14,15]. On the other hand, the three tools mentioned above have been also used to generate limit cycles from the critical point, see for instance [15][16][17], respectively.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…Let N(n) be the maximum possible number of limit cycles bifurcating from nilpotent critical points for analytic vector fields of degree n. The authors of [16] got N(3) ≥ 2, N(5) ≥ 5, N(7) ≥ 9; The authors of [15] got N(3) ≥ 3, N(5) ≥ 5; For a family of Kukles system with six parameters, the authors of [17] got N(3) ≥ 3. The authors of [21,22] got N(3) ≥ 7 and N(3) ≥ 8, respectively.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…In [10], Takens proved that Lyapunov system can be formally transformed into a generalized Liénard system. Furthermore, in [11], Álvarez and Gasull proved that the generalized Lienard system could be simplified even more by a reparametrization of the time. At the same time, Giacomini et al [12,13] proved that the analytic nilpotent systems with a center can be expressed as limit of non-degenerate systems with a center.…”
Section: Introductionmentioning
confidence: 99%
“…Let N(n) be the maximum possible number of limit cycles bifurcating from nilpotent critical points for analytic vector fields of degree n. It was found that N(3) ≥ 2, N(5) ≥ 5, N(7) ≥ 9 in [23], N(3) ≥ 3, N(5) ≥ 5 in [17], and for Kukles system with six parameters N(3) ≥ 3 in [11]. Recently, Yirong Liu and Jibin Li proved that N(3) ≥ 8 in [24].…”
Section: Introductionmentioning
confidence: 99%
“…Este caso é um dos mais investigados até hoje, com grande número de artigos publicados a respeito -cf. [1,2,23,25,29];…”
Section: Introductionunclassified